Detection of some virulence factors among Candida albicans isolated from patients and prevalence of candidalysin gene ECE1 - Safaa A. S. Al-Qaysi; Sokayna R. M. AL-Rubaie AL-Rubaie (مجلة بغداد للعلوم)
Candida albicans is a common cause of respiratory infection and oral candidiasis in people; it is an opportunistic yeast pathogen and a major cause of morbidity and mortality in the immunocompromised persons and causes superficial infections of mucosal surfaces which affect millions of people throughout world. The main goal of this study was investigating the prevalence of some virulence factors which has the ability to configure biofilm formation, proteinase, hemolysin production among C.albicans isolates that include prevalence of candidalysin gene Eec1. Samples were collected during the period May and August of 2022 from 280 samples (swabs) of different ages and sexes of non-duplicated Iraqi patients suffering from oral candidiasis and respiratory diseases. The results showed that 102 were positive samples, 58(56.86%) from oral cavity and 44 (43.14%) from respiratory tract, while 178 of them were negative. Candida isolates were identified using conventional methods by grown on HiCrome Candida medium, germ tube production, chlamydospore formation and confirmed using VITEK-2 system, susceptibility of Candida isolates to antifungal drugs was examined by disk diffusion method, performed as recommended by (CLSI) M44-A document. The isolates showed a high level of susceptibility to Amphotericin-B (93.20%), Nystatin (90.20%), and Clotrimazole (85.92%). Prevalence of Candidalysin gene Eec1 among 70 isolates of C. albicans was investigated using polymerase chain reaction (PCR) technique, the results revealed that 41(58.57%) were harboring Ece1 gene for the oral cavity and respiratory tract. Only 34 (48.57%) C. albicans isolates were strong producer of biofilm, while 30 (42.86%) isolates produced proteinase, 20 (28.57%) of isolates had the ability to hemolyze the blood.